DEIXIS IN SONG LYRICS OF FLYING WITHOUT WINGS ALBUM BY WESTLIFE - Halawa, Intan Putri Sari (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
This research was aim to analyze the Deixis in Song Lyrics of“Flying Without Wings album” by Westlife. This research designed by using qualitative descriptive method. In analyzing the data, the research used theory of Creswell (2009:172-176). The data source of this study was taken fromthe Song Lyrics Album Flying Without Wings by Westlifethat was obtained from the internet, downloaded the lyrics from the internet. The data of this study isdeixis that found in the song lyrics Album Flying Without Wings ByWestlife. To examine the credibility of this study the researcher used triangulation such as data triangulation, investigator triangulation and theory triangulation. Based on the result ofresearch there were13 Personal Deixis, 5time deixis, 3 place deixis, 1 discourse deixis. It can be concluded that the dominant deixisused in song lyrics of “Flying Without Wing Album” by Westlife is personal deixis are 13. It is expected that all song lovers, teacher, students and next researcher use the result of this research as the sources of the knowledge is the term of deixis.